Pemanfaatan Ekosistem Pesisir Dalam Eksplorasi Pengetahuan Lokal Tumbuhan Obat Berbasis Komunitas Etnis Bajo Torosiaje Serumpun - Abubakar Sidik Katili; Ramli Utina; Lilan Dama; Ilyas H. Husain (The Ethnobiological Society of Indonesia, 2021)
Bajo ethnicity is one of the ethnic groups in Gorontalo province which is known as a community that is very thick with coastal areas. This is because of the existence of this ethnic village which is above the coastal waters of the bay tomini and is about 600 meters from land. Bajo ethnicity has a wealth of local knowledge related to the utilization of medicinal plants. That knowledge is a legacy passed down over a long period of time. This study aims to explore plants that are used as medicine and a form of local knowledge in the Bajo Ethnic community. This study was conducted in Torosiaje Village, Popayato District, Pohuwato Regency within two months. The study method used is descriptive qualitative. Data retrieval techniques were conducted with in-depth interviews on 13 traditional sculptors (hattra) of bajo ethnic to explore medicinal plants and local knowledge in traditional practice. This study found 41 types of medicinal plants, with parts of plants used, namely leaves, flowers, fruit, fruit peels, stems, and roots. Found also 53 types of traditional herbs. In terms of local knowledge, found 19 forms of local knowledge of bajo ethnicity in utilizing medicinal plants as well as with medicinal rituals that use medicinal plants. Bajo ethnicity is classified as an ethnicity that still holds values and norms derived from ancestors and has local knowledge in utilizing surrounding plants for treatment.